2015
DOI: 10.1117/1.jbo.20.6.065003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the validity of 3 × 3 Mueller matrix decomposition

Abstract: Abstract. Using Monte Carlo simulations based on previously developed scattering models consisting of spherical and cylindrical scatterers imbedded in birefringent interstitial medium, we compare the polarization parameters extracted from the 3 × 3 and 4 × 4 Mueller matrix decomposition methods in forward and backward scattering directions. The results show that the parameters derived from the 3 × 3 Mueller matrix decomposition are usually not the same as those from the 4 × 4 Mueller matrix decomposition but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The anisotropic biological elements in the ECM (particularly collagen and elastin) have been simulated with several materials, including silk 88,99 and glass fibers. 98,107 An example of fibrous phantom is shown in Fig. 3.…”
Section: Retarding Phantomsmentioning
confidence: 99%
“…The anisotropic biological elements in the ECM (particularly collagen and elastin) have been simulated with several materials, including silk 88,99 and glass fibers. 98,107 An example of fibrous phantom is shown in Fig. 3.…”
Section: Retarding Phantomsmentioning
confidence: 99%
“…The assumptions -especially the latter two -cannot be satisfied in many cases, especially for anisotropic tissues. Based on Monte Carlo simulation and tissue phantom studies, Wang et al assessed the difference between the results obtained from 3 3 3 Mueller matrix decomposition [204] and 4 3 4 Mueller polar decomposition [205], and found that the parameters derived from the 3 3 3 Mueller matrix decomposition are usually not the same as those from the 4 3 4 Mueller matrix decomposition but demonstrate similar qualitative relations to changes in the microstructure of the sample, such as the density, size, and orientation distributions of the scatterers, and birefringence of the interstitial medium. Another emerging interpretation method named "Mueller matrix transformation method" introduced in Section 5.3 may be more promising to extract the useful linear depolarization and retardance related information of tissue from 3 3 3 Mueller matrix images.…”
Section: 3 3 Mueller Polarimetric Endoscopementioning
confidence: 99%
“…However, it is not trivial to take the 4 × 4 Mueller matrices at different wavelengths using the current experimental setup. Also, decomposition of the 3 × 3 Mueller matrix results shows large discrepancies in the set of parameters [27]. Therefore, we use the MMT parameters A and b, which are only linked to the linear polarization Mueller matrix elements, i.e.…”
Section: Mueller Matrix Transformation (Mmt) Parametersmentioning
confidence: 99%